Site-Specific Fluorescent Labeling of Antibodies and Diabodies Using SpyTag/SpyCatcher System for In Vivo Optical Imaging. - Alam, Md. Kausar; El-Sayed, Ayman; Barreto, Kris; Bernhard, Wendy; Fonge, Humphrey; Geyer, C. Ronald (Molecular Imaging & Biology, 2019)
Purpose: Construction of antibody-based, molecular-targeted optical imaging probes requires the labeling of an antibody with a fluorophore. The most common method for doing this involves non-specifically conjugating a fluorophore to an antibody, resulting in poorly defined, heterogeneous imaging probes that often have suboptimal in vivo behavior. We tested a new strategy to site-specific label antibody-based imaging probes using the SpyCatcher/SpyTag protein ligase system.Procedures: We used the SpyCatcher/SpyTag protein ligase system to site specifically label nimotuzumab, an anti-EGFR antibody and an anti-HER3 diabody. To prevent the labeling from interfering with antigen binding, we introduced the SpyTag and SpyCatcher at the C-terminus of the antibody and diabody, respectively. Expression and binding properties of the C-terminal antibody-SpyTag and diabody-SpyCatcher fusions were similar to the antibody and diabody, indicating that the SpyTag and SpyCatcher fusions were well tolerated at this position. Site-specific labeling of the antibody and diabody was performed in two steps. First, we labeled the SpyCatcher with IRDye800CW-Maleimide and the SpyTag with IRDye800CW-NHS. Second, we conjugated the IRDye800CW-SpyCatcher and the IRDye800CW-SpyTag to the antibody or diabody, respectively. We confirmed the affinity and specificity of the IRDye800CW-labeled imaging probes using biolayer interferometry and flow cytometry. We analyzed the in vivo biodistribution and tumor accumulation of the IRDye800CW-labeled nimotuzumab and anti-HER3 diabody in nude mice bearing xenografts that express EGFR and HER3, respectively.Results: Expression and binding properties of the C-terminal antibody-SpyTag and diabody-SpyCatcher fusions were similar to the antibody and diabody, indicating that the SpyTag and SpyCatcher fusions were well tolerated at this position. We confirmed the affinity and specificity of the IRDye800CW-labeled imaging probes using biolayer interferometry and flow cytometry. We analyzed the in vivo biodistribution and tumor accumulation of the IRDye800CW-labeled nimotuzumab and anti-HER3 diabody in nude mice bearing xenografts that express EGFR and HER3, respectively. Site-specifically IRDye800CW-labeled imaging probes bound to their immobilized targets, cells expressing these targets, and selectively accumulated in xenografts.Conclusions: These results highlight the ease and utility of using the modular SpyTag/SpyCatcher protein ligase system for site-specific fluorescent labeling of protein-based imaging probes. Imaging probes labeled in this manner will be useful for optical imaging applications such as image-guided surgery and have broad application for other imaging modalities.